2019
DOI: 10.1001/jamaneurol.2018.4882
|View full text |Cite
|
Sign up to set email alerts
|

Spaceflight-Associated Brain White Matter Microstructural Changes and Intracranial Fluid Redistribution

Abstract: IMPORTANCE Spaceflight results in transient balance declines and brain morphologic changes; to our knowledge, the effect on brain white matter as measured by diffusion magnetic resonance imaging (dMRI), after correcting for extracellular fluid shifts, has not been examined. OBJECTIVE To map spaceflight-induced intracranial extracellular free water (FW) shifts and to evaluate changes in brain white matter diffusion measures in astronauts. DESIGN, SETTING AND PARTICIPANTS We performed retrospective, longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
134
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(146 citation statements)
references
References 55 publications
11
134
0
1
Order By: Relevance
“…This finding is consistent with the known role of the splenium of the corpus callosum in mediating fast visuomotor responses. 26 In astronauts, abnormal diffusion metrics involving multiple white matter tracts indicative of disrupted white matter connectivity have been identified postflight, 27 and in particular, a recent study found focally reduced fractional anisotropy within the right posterior thalamic radiation in astronauts postflight, a physiologic correlate to the local volume change we identify here. 28 Initially, we had hypothesized that ventricular enlargement postflight would correlate with the development of SANS; however, the 4 astronauts with ophthalmologic changes had a smaller change in %DVV than those without SANS (12.8% versus 6.5%, P = .02, n = 8 versus n = 4).…”
Section: Discussionsupporting
confidence: 59%
“…This finding is consistent with the known role of the splenium of the corpus callosum in mediating fast visuomotor responses. 26 In astronauts, abnormal diffusion metrics involving multiple white matter tracts indicative of disrupted white matter connectivity have been identified postflight, 27 and in particular, a recent study found focally reduced fractional anisotropy within the right posterior thalamic radiation in astronauts postflight, a physiologic correlate to the local volume change we identify here. 28 Initially, we had hypothesized that ventricular enlargement postflight would correlate with the development of SANS; however, the 4 astronauts with ophthalmologic changes had a smaller change in %DVV than those without SANS (12.8% versus 6.5%, P = .02, n = 8 versus n = 4).…”
Section: Discussionsupporting
confidence: 59%
“…Another retrospective analysis of the brain MRI scans of 15 astronauts has also shown significant widespread spaceflightassociated free water increases at the base of the cerebellum and decrease along the posterior vertex which was reflecting disrupted white matter structural connectivity in the cerebellum, corticospinal tract and superior longitudinal fasciculus, among other regions after adjustment. 43 Unfortunately, some of the clinical and radiographic findings in SANS may not be unique to only LDSF because many of the astronauts thus far studied had previous SDSF and thus had no true pre-flight comparative data. In addition, some of the MRI findings (e.g., globe flattening) may be subtle and could easily be over-interpreted especially if the neuroradiologist is not masked to their flight status.…”
Section: Introductionmentioning
confidence: 99%
“…34 This is supported by transcriptomic and proteomic analysis of brain in mice models, 22,35,36 and more recently in humans by magnetic resonance imaging. 4,[37][38][39][40] As also proposed in the field of neurodegenerative disorders, an impairment of the BBB is suggested to induce or accelerate the processes of the memory impairments. 17 Our work participates to confirm the link between BBB dysfunction induced by gravity changes and putative memory impairments hypothesized recently, 15 yet this point should be investigated to understand its molecular basis.…”
Section: Discussionmentioning
confidence: 98%